Permitting and Licensing Regimes for Renewable Energy Projects - Merle-Beral, Elena; Gassner, Katharina (World Bank, Washington, DC, 2015)
Permitting, licensing, and other authorization procedures are an integral part of investing in renewable energy. For private companies, the quality of these procedures can drastically affect transaction costs and project risk. Optimal regimes are tailored to country specifics and depend on the way in which private investors access the market in the first place—from auctions to site-specific tenders to standardized contracts on a first-come, first-served basis. Although there is no single best practice when it comes to authorizing renewable energy projects, common principles exist that signal an investor-friendly and socially and environmentally responsible regime.